The early years movement handbook : a principles-based approach to supporting young children's physical development, health and wellbeing - Manners, Lala (Jessica Kingsley Publishers, 2019)
The go-to professional resource for understanding the importance of children's physical development and enhancing it in a structured way. Eight principles explain why physical activity is so important for children's lifelong development, and a workable framework is provided for the design and delivery of practical sessions.